2012
DOI: 10.1016/j.jval.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Alzheimer's Disease Severity and Longitudinal Costs

Abstract: Potential endogeneity should be controlled for to prevent biased estimations of the impact of AD severity measures on costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 34 publications
(53 reference statements)
9
50
3
1
Order By: Relevance
“…A total of 47 studies reported economic data on the direct and indirect costs of AD for the seven selected countries; the remaining five studies reported aggregated international data [50][51][52][53][54]. Among the 47 studies, 17 primary source articles were identified in which cost component data were available and presented according to AD severity or patients' living conditions; two for France [55,56], four for Germany [7,[57][58][59], zero for Italy, three for the Netherlands [8,51,60], four for Spain [49,[61][62][63], two for the UK [64,65], and two for the USA [9,66]. Studies in which cost components were presented by patients' living conditions were included [51,57,59,60] as patients with higher AD severity are more frequently institutionalized than other AD patients [67].…”
Section: Economic (Direct and Indirect Costs)mentioning
confidence: 99%
“…A total of 47 studies reported economic data on the direct and indirect costs of AD for the seven selected countries; the remaining five studies reported aggregated international data [50][51][52][53][54]. Among the 47 studies, 17 primary source articles were identified in which cost component data were available and presented according to AD severity or patients' living conditions; two for France [55,56], four for Germany [7,[57][58][59], zero for Italy, three for the Netherlands [8,51,60], four for Spain [49,[61][62][63], two for the UK [64,65], and two for the USA [9,66]. Studies in which cost components were presented by patients' living conditions were included [51,57,59,60] as patients with higher AD severity are more frequently institutionalized than other AD patients [67].…”
Section: Economic (Direct and Indirect Costs)mentioning
confidence: 99%
“…Available cost studies from several European countries show a strong positive relationship between disease severity and total costs of care [1,[3][4][5][6][7][8]. Informal care costs form the major component of societal costs for community-dwelling AD dementia patients [8][9][10][11], and the cost of institutional care is the other main cost driver in the long-term care of patients with AD dementia [12].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of BPSD was evaluated by means 155 of the Neuropsychiatric Inventory (NPI) [27], which Finally, anosognosia was assessed using the 163 Anosognosia Questionnaire-Dementia (AQ-D) [28], [33][34]. This approach enabled us to examine the …”
mentioning
confidence: 99%